On the importance of trait interrelationships for understanding environmental responses of stream macroinvertebrates. (3rd December 2015) - Pilière, A. F. H.; Verberk, W. C. E. P.; Gräwe, M.; Breure, A. M.; Dyer, S. D.; Posthuma, L.; de Zwart, D.; Huijbregts, M. A. J.; Schipper, A. M.
Summary: Biological traits of organisms are expected to provide increased mechanistic understanding of species–environment relationships. Linking traits to environmental conditions is, however, not straightforward, as traits are interconnected within species and can affect the adaptive value of each other. The aim of our study was to evaluate the importance of these trait interrelationships for understanding environmental responses of freshwater macroinvertebrates. To this end, we investigated whether environmental responses of macroinvertebrates sharing a given trait were consistent or differed according to their taxonomy or to their other traits. We divided the macroinvertebrates into groups based on single traits (49 single‐trait modalities), on taxonomy (10 orders) and on their overall trait profile (10 trait profile groups [TPGs], defined using self‐organising maps clustering). Abundances of each of these 69 groups were related to 24 environmental variables using boosted regression tree (BRT) modelling, to assess the environmental responses of single traits, orders and TPGs. Cross‐validated predictive power ( R 2 ) of the BRT models ranged from < 1% to 38%. Environmental responses of macroinvertebrates sharing a given trait were inconsistent and varied according to order and/or TPG. Single‐trait responses often reflected the responses of the most abundant taxonomic group expressing the trait, suggesting that analysis of trait responses simply revealed patterns in habitat use by the most abundant species and not necessarily mechanistic relationships. Further, taxa from the same TPG (hence showing large overlap in their traits) but belonging to different orders showed different environmental responses. This indicates that the order a taxon belongs to confers unique information related to its evolutionary history that was not captured by our 49 trait modalities. However, groupings by orders cannot replace trait‐based approaches, since TPGs also revealed differences in trait profiles within some orders, which were associated with different environmental responses. Our results highlight the importance of considering multiple rather than single traits when linking macroinvertebrates to environmental variables, including the potential information conveyed by evolutionary history.